THE EFFECT OF WORKLOAD, COMPENSATION AND WORKING FLEXIBILITY ON EMPLOYEE PERFORMANCE AT PT PURNAMA INFONESIA SIDOARJO - Agus Sunaryo (Jurnal Ekonomi, 2023)
This study aims to determine the Effect of Work Load, Compensation, and Flexibility of Working Hours on Employee Performance at PT. Indonesian Full Moon. Probability sampling is the method used for sampling. There were 20 people who participated in this research sample. Product Solutions and Services Statistics Program (SPSS) Version 29 was used for the multiple linear regression analysis used in this study. Work Load, Compensation, and Work Hour Flexibility all have a significant effect on employee performance, as research shows, as does partial Work Load, which has a positive and significant impact on employee performance. PT. Indonesian Full Moon. Meanwhile, compensation and flexibility of working hours have no effect on performance at PT. Indonesian Full Moon.